A multifunctional supramolecular hydrogel for infected wound healing. (16th December 2021) - Ding, Tingting; Qi, Jiajia; Zou, Jingcheng; Dan, Hongxia; Zhao, Hang; Chen, Qianming
Abstract : Infected wound healing has been a concern so it is crucial to develop new multifunctional hydrogel that integrates antibacterial, adhesive and antioxidant properties. Abstract : Bacterial infection poses a significant threat to wound healing, and the preparation of novel wound dressings is very important. However, currently reported dressings serve as traditional physical barriers or functional ones with limited effects, such as antibacterial effect or adhesion. There is growing demand for developing wound dressing materials with antibacterial effect, good adhesion, proper degradation within the wound recovery time, and simple synthesis. In this study, based on a natural plant extract – tannic acid (TA) and natural guanosine (G), a supramolecular soft hydrogel (G-TA hydrogel) was successfully synthesized based on dynamic borate esters in a one-pot reaction. The hydrogel showed excellent antibacterial and adhesive properties and could be degraded within three days in vivo . In addition, the G-TA hydrogel also showed remarkable antioxidant capability, excellent injectability, a long in vitro lifespan, and good cytocompatibility on L929 cells. Furthermore, the hydrogel could accelerate the healing of full-thickness wounds on the back skin of mice, indicating its promising applications in wound repair.